Pakistani-American Relations During The South Asia Crisis Of 1971 - Kayani, Mansoor Ahmed (My University, 2014)
The aim of this study was to investigate the U.S policy regarding the 1971 crisis of East Pakistan. The 1971 East Pakistan crisis provides important information on the U.S. Pakistan alliance during the Cold War. Both countries needed each other's support to protect their Cold War interests. Therefore, the U.S. support for Pakistan in the 1971 crisis in East Pakistan was designed to protect the American security interests in Asia. The U.S. alliance with Pakistan necessitated that the U.S. to provide aid and support to Pakistan during the 1971 crisis. The foreign relations of the United States (FRUS) documents published by the office of historians and Department of State have an extensive list of the U.S. government documents. These documents deal with the 1971 crisis of East Pakistan and provide an important study on the subject. These documents were consulted as primary resources to conduct the research on the 1971 crisis. The research concludes that the U.S. favored Pakistan in the 1971 crisis was to protect the U.S. interests such as the opening with China, the war of Vietnam and to counter the Indian-Soviet alliance. Meanwhile, Pakistan also needed the U.S. alliance to protect its security as it arch rival India was allied with the Soviet Union. Both the U.S. and Pakistan were united to deal with the Indian and the Soviet threat in the 1971 crisis of East Pakistan. The significant of the finding concludes that Pakistan was an important strategic country to the U.S. during the Cold War' who helped to protect the U.S. security interests in Asia.
Keywords: History